A 3D printable perfused hydrogel vascular model to assay ultrasound-induced permeability. (16th May 2022) - Royse, Madison K.; Means, A. Kristen; Calderon, Gisele A.; Kinstlinger, Ian S.; He, Yufang; Durante, Marc R.; Procopio, Adam T.; Veiseh, Omid; Xu, Jun
Abstract : To examine the impact of ultrasound transduction on endothelial barrier function, a 3D printable perfused hydrogel vascular model was developed to assess endothelial permeability and enable live imaging of cell–cell junctions. Abstract : The development of an in vitro model to study vascular permeability is vital for clinical applications such as the targeted delivery of therapeutics. This work demonstrates the use of a perfusion-based 3D printable hydrogel vascular model as an assessment for endothelial permeability and its barrier function. Aside from providing a platform that more closely mimics the dynamic vascular conditions in vivo, this model enables the real-time observation of changes in the endothelial monolayer during the application of ultrasound to investigate the downstream effect of ultrasound-induced permeability. We show an increase in the apparent permeability coefficient of a fluorescently labeled tracer molecule after ultrasound treatment via a custom MATLAB algorithm, which implemented advanced features such as edge detection and a dynamic region of interest, thus supporting the use of ultrasound as a non-invasive method to enhance vascular permeability for targeted drug therapies. Notably, live-cell imaging with VE-cadherin-GFP HUVECs provides some of the first real-time acquisitions of the dynamics of endothelial cell–cell junctions under the application of ultrasound in a 3D perfusable model. This model demonstrates potential as a new scalable platform to investigate ultrasound-assisted delivery of therapeutics across a cellular barrier that more accurately mimics the physiologic matrix and fluid dynamics.